Effect of Pellet Cooling Method, Sample Preparation, Storage Condition, and Storage Time on Phytase Activity of a Swine Diet - M. Saensukjaroenphon; C. E. Evans; C. R. Stark; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2020)
Temperature and moisture content have been identified as two factors that influence enzyme inactivation. Phytase may be further degraded in feed samples if there is moisture left in the sample and it is not properly stored prior to analysis. Therefore, the objective of this experiment was to determine the effect of cooling method, sample preparation, storage condition, and storage time on phytase stability. In Exp. 1, treatments were arranged in 2 × 2 factorial with main effects of sample preparation (none or freeze-dried) and storage condition (ambient storage or freezer storage). Diets were mixed 3 separate times to provide 3 replicates per treatment. The result of Exp. 1 demonstrated that there was no interaction between drying process and storage condition for mash samples collected from the mixer. The sample drying process and storage condition did not impact the phytase stability. In Exp. 2, treatments were arranged in a 2 × 3 factorial with main effects of cooling method (counterflow cooler or freezer) and sample preparation (non-dried then freezer storage, freeze-dried then freezer storage, freeze-dried then ambient storage). The diet was steam conditioned for approximately 45 s at 185°F using a 5.1- × 35.8-in single shaft conditioner of a pellet mill (California Pellet Mill model Cl-5, Crawfordsville, IN) at a production rate of 2.2 lb/min by holding the feeder at a constant speed setting. The sample was collected at the end of the conditioner and did not pass the pellet die. The conditioner was run 3 separate times to provide 3 replicates for each treatment. The result of Exp. 2 demonstrated that there was no interaction between the cooling method and sample preparation for phytase stability of conditioned mash samples. The cooling method and sample preparation did not affect the phytase stability. In Exp. 3, treatments were arranged in a 5 × 3 × 2 factorial with main effects of cooling method (none, heat diffusion, experimental fan cooler, experimental counterflow cooler, or freezer), storage condition (ziplock/ ambient, ziplock/frozen, and vacuum/frozen), and storage time (1 or 3 wk.). The diet was steam conditioned for approximately 45 s at 185°F and pelleted using a pellet mill (California Pellet Mill model Cl-5, Crawfordsville, IN) equipped with 0.16- × 0.50-in die. The diet was pelleted at a production rate of 2.2 lb/min by holding the feeder at a constant speed setting. The pellet mill was run 3 separate times to provide 3 replicates for each treatment. The result of Exp. 3 demonstrated that there were no three-way and two-way interactions among cooling method, storage condition, and storage time (P>0.686). The cooling method, storage condition, and storage time did not impact phytase stability (P>0.348). Therefore, freeze-drying, vacuum sealing, and freezing were not required when the feed samples were analyzed within 3 weeks of production. However, conditioned mash and hot pellet samples should be dried prior to sending the samples to the lab to prevent mold growth.
Keywords: phytase activity; phytase stability; sample preparation; sample storage